Application of Basic Science to Develop Cognitive Children Age 5-6 Years at Al-Ikhsan Bore Kindergarten in 2023 - Evi Ariani Sutomo; Good Nilawati Astini; Nurhasanah; Gunawan (Syntax Corporation Indonesia, 2023)
This research is motivated by the application of monotonous learning methods to develop children's cognitive abilities, especially in the field of children's science. The dominant cognitive development of children developed at Al-Ikhsan Bore Kindergarten is symbolic development. Based on these problems, this research aims to find out how to apply early science to develop the cognitive development of children aged 5-6 years at TK Al-Ikhsan Bore in 2023. The type of research used is qualitative research with subjects of 11 boys and 9 girls aged 5-6 years. To obtain data in this research using observation, interviews and documentation methods. The data analysis technique used is descriptive qualitative. In this research, there are steps in its implementation, namely: First, preparation for preparing tools and materials during grain planting activities, making children's learning results sheets and preparing students to take part in the activity. Second, an opener to open children's horizons. Third, the activity was carried out for six days with the activity of observing plant growth and comparing plant growth and fourth, namely closing, to ask again about the lessons that had been learned and carried out. The results of the research in the application of early science to develop cognitively, namely by using 13 indicators that have been observed, namely that there are 5 children in the beginning to develop (MB) category, 9 children are categorized as developing according to expectations (BSH) and 5 children are developing very well (BSB). Based on the results of this research, it can be concluded that the activity of planting grain which is carried out correctly and regularly can develop children's cognitive abilities.